Hippocampal circuits underlie improvements in self‐reported anxiety following mindfulness training. Issue 9 (23rd July 2020) - Sevinc, Gunes; Greenberg, Jonathan; Hölzel, Britta K.; Gard, Tim; Calahan, Thomas; Brunsch, Vincent; Hashmi, Javeria A.; Vangel, Mark; Orr, Scott P.; Milad, Mohammed R.; Lazar, Sara W.
Abstract: Introduction: Mindfulness meditation has successfully been applied to cultivate skills in self‐regulation of emotion, as it employs the unbiased present moment awareness of experience. This heightened attention to and awareness of sensory experience has been postulated to create an optimal therapeutic exposure condition and thereby improve extinction learning. We recently demonstrated increased connectivity in hippocampal circuits during the contextual retrieval of extinction memory following mindfulness training. Methods: Here, we examine the role of structural changes in hippocampal subfields following mindfulness training in a randomized controlled longitudinal study using a two‐day fear‐conditioning and extinction protocol. Results: We demonstrate an association between mindfulness training‐related increases in subiculum and decreased hippocampal connectivity to lateral occipital regions during contextual retrieval of extinguished fear. Further, we demonstrate an association between decreased connectivity and decreases in self‐reported anxiety following mindfulness training. Conclusions: The results highlight the role of the subiculum in gating interactions with contextual stimuli during memory retrieval and, also, the mechanisms through which mindfulness training may foster resilience. Abstract : Mindfulness meditation has successfully been applied to cultivate skills in self‐regulation of emotion, as it employs the unbiased present moment awareness of experience. This heightened attention to and awareness of sensory experience has been postulated to create an optimal therapeutic exposure condition and thereby improve extinction learning. Here, we examine the role of structural changes in hippocampal subfields and further demonstrate an association between mindfulness training‐related increases in subiculum and decreased hippocampal connectivity to lateral occipital regions during contextual retrieval of extinguished fear. Further, we demonstrate an association between decreased connectivity and decreases in self‐reported anxiety following mindfulness training. These results highlight the role of the subiculum in gating interactions with contextual stimuli during memory retrieval and, also, the mechanisms through which mindfulness training fosters resilience.